The Correlation Between Learning Motivation And Reading Comprehension Achievement at The X Grade Students of SMAN 8 Bekasi - Ferawaty Puspitorini (International Journal of English and Applied Linguistics (IJEAL), 2021)
This research was conducted to measure whether there is a correlation between learning motivation and reading comprehension achievement. The population of this research is the first-grade students of SMAN 8 Bekasi that consists of 99 students and was divided into three classes. The total samples are 40 students taken from the entire population by simple random sampling. The method was used in this research is a survey. It means quantitative analysis by using a questionnaire to a lot of objects. In his study, the writer gave questionnaires that consist of forty questions to know their learning motivation. And then, the writer gave multiple-choice tests to know reading comprehension achievement. The result of the calculation of correlation coefficient Phi with 5% level of significant from the degree of freedom (df) = N is 3, 841 and the interpretation of the score 2 count  and  2 table  indicated that  2 count (32, 727) >  2 table (3,841). Based on the result above, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. There is a correlation between learning motivation and reading comprehension achievement among the X grade students of SMAN 8 Bekasi.